Low Pt-content ternary PdCuPt nanodendrites: an efficient electrocatalyst for oxygen reduction reaction. Issue 3 (5th January 2017) - Fu, Shaofang; Zhu, Chengzhou; Song, Junhua; Zhang, Peina; Engelhard, Mark H.; Xia, Haibing; Du, Dan; Lin, Yuehe
Abstract : Low Pt-content ternary PdCuPt nanodendrites with enhanced electrocatalytic performance for oxygen reduction reaction are synthesized in aqueous solution using PdCu nanodendrites as templates. Abstract : Dendritic nanostructures are capturing increasing attention in electrocatalysis owing to their unique structural features and low density. Herein, we report for the first time, bromide ion mediated synthesis of low Pt-content PdCuPt ternary nanodendrites via galvanic replacement reaction between a Pt precursor and a PdCu template in aqueous solution. The experimental results show that the ternary PdCuPt nanodendrites present enhanced electrocatalytic performance for oxygen reduction reaction in acid solution compared with commercial Pt/C as well as some state-of-the-art catalysts. In detail, the mass activity of the PdCuPt catalyst with optimized composition is 1.73 A mgPt −1 at 0.85 V vs. RHE, which is 14 times higher than that of a commercial Pt/C catalyst. Moreover, the long-term stability test demonstrates its better durability in acid solution. After 5k cycles, there is still 70% electrochemical surface area maintained. This method provides an efficient method to synthesize trimetallic alloys with controllable composition and specific structure for oxygen reduction reaction.